5(3+8)=(X*3)+(X*8)

Simple and best practice solution for 5(3+8)=(X*3)+(X*8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3+8)=(X*3)+(X*8) equation:


Simplifying
5(3 + 8) = (X * 3) + (X * 8)

Combine like terms: 3 + 8 = 11
5(11) = (X * 3) + (X * 8)

Multiply 5 * 11
55 = (X * 3) + (X * 8)

Reorder the terms for easier multiplication:
55 = (3X) + (X * 8)

Reorder the terms for easier multiplication:
55 = (3X) + (8X)

Combine like terms: (3X) + (8X) = 11X
55 = 11X

Solving
55 = 11X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-11X' to each side of the equation.
55 + -11X = 11X + -11X

Combine like terms: 11X + -11X = 0
55 + -11X = 0

Add '-55' to each side of the equation.
55 + -55 + -11X = 0 + -55

Combine like terms: 55 + -55 = 0
0 + -11X = 0 + -55
-11X = 0 + -55

Combine like terms: 0 + -55 = -55
-11X = -55

Divide each side by '-11'.
X = 5

Simplifying
X = 5

See similar equations:

| 8r+9r=-21 | | (2x-8)-10=2-8x | | 9x+40=x-16 | | 5h(p)+25=20h(p) | | 3(n+7)=7-4(n-7) | | 8xsquared-47x-6=0 | | 2+8=33(2x) | | 5h+25=20h | | X^2-8x+6=f(x) | | 7(4m-3)= | | f(x)=x^2-9x^4 | | 127=4(2*c) | | 264/26 | | 127=4+2c | | 12m+4m-3m= | | x-25.4=59.6 | | 3+7=5+v | | 3/8y-1/6=1/5 | | 375/800 | | 4n=n-21 | | 48a^3k2/6a^2k | | 775/800 | | 5p-2(-p-1)-7=p-(-8-p)-12 | | x^3-3/2y=0 | | -3(x+8)-2=52 | | r=47 | | 33+3n=-8(4n-5) | | 9a+2a=3a-4x | | 12+4=-4(8x-4) | | -15x-3=-3x+5 | | =1x^2+9x | | 42x=35 |

Equations solver categories